Strategi UMKM untuk Meningkatkan Perekonomian selama Pandemi Covid-19 pada saat New Normal - Safira Aliyani Firdaus; Igo Fadilah Ilham; Liza Putri Aqidah; Safir Aliyani Firdaus; Setyani Agung Dwi Astuti; Imam Buchori (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2020)
This study aims to determine and analyze the appropriate strategies to improve the economy of MSMEs when new normal is applied due to the impact of the Covid-19 pandemic.. The results obtained from this study indicated that there was a need for fast, precise and tangible steps from the government and business actors to overcome the losses that have occurred due to the pandemic and to make updates and evaluations of the business cycle following the current conditions so that businesses can continue to survive and develop.